Islam in South Asia : a short history - Malik, Jamal (Themes in Islamic studies, 2008)
"Islamic South Asia has become a focal point in academia. Where did Muslims come from? How did they fare in interacting with Hindu cultures? How did they negotiate identity as ruling and ruled minorities and majorities?"--Jacket